Artistic function of detail in Kazakh prose - Gulnaz Tokshylykova, Gulmira Satylkhanova, Alya Tanzharykova, Nurbol Khudaibergenov,; Taimanova, Sara (Opción, 2019)
The artistic detail plays an important role in the transmission of artistic thought. For this reason, the article is aimed to determine the essence and importance of detail on the basis of national knowledge and concepts via comparative historical research method. As a result, in folk historical works there are a huge number of artistic details of the ethnocultural nature. In conclusion, the independent and original place of each nation in the system of universal values is determined only by the ethnocultural features inherent in these people.